DEVELOPING INTERCULTURAL COMPETENCE IN FOREIGN LANGUAGE CLASSES: PEDAGOGICAL APPROACHES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
In the modern globalized world, communication between representatives of different cultures has become an integral part of social, economic, and educational processes. Foreign language education is no longer limited to teaching linguistic structures and vocabulary; it also involves the development of intercultural competence. Intercultural competence enables learners to interact effectively and appropriately with people from different cultural backgrounds. This article explores pedagogical approaches to developing intercultural competence in foreign language classrooms. The study examines theoretical foundations of intercultural communication, the role of cultural awareness in language learning, and modern teaching methods that promote intercultural understanding. Special attention is given to interactive teaching strategies, project-based learning, authentic materials, and digital technologies that facilitate intercultural dialogue. The article also highlights the importance of integrating cultural elements into language curricula and preparing teachers to foster intercultural learning environments. The findings suggest that effective intercultural competence development requires a holistic pedagogical framework combining linguistic knowledge, cultural awareness, critical thinking, and communicative skills. Implementing these approaches can significantly enhance students’ ability to participate in global communication and develop tolerance toward cultural diversity.